Literature Review on the Ethical Use of ChatGPT in Buddhist Religious Education - Acep, Lauw; Philo Chandra, Derioniel (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The rapid adoption of ChatGPT in education raises various ethical concerns, especially within the context of Buddhist Religious Education, which emphasizes moral and spiritual values. This study aims to examine the ethical use of ChatGPT in Buddhist Religious Education based on the principles of the Dhamma. The research employs a literature review method with a descriptive-comparative approach, analyzing Buddhist canonical texts such as the Tipiṭaka and recent scholarly articles on AI ethics. The findings reveal that Buddhist ethics differ from secular ethics by focusing on intention, mental awareness, and spiritual transformation, rather than merely consequences or rule-based obligations. Comparatively, secular ethics tend to be consequentialist and deontological, while Buddhist ethics are rooted in inner qualities and moral harmony. Based on this comparison, the proposed solution is to promote the wise and mindful use of ChatGPT as a supportive tool—rather than a replacement for teachers—while upholding the teacher's role as a moral and spiritual guide. Furthermore, the integration of core values such as wisdom (paññā), honesty (sacca), and mindfulness (sati) is essential in the learning process. Future research is recommended to empirically examine the effectiveness of these ethical guidelines in the context of Buddhist education.